Modelagem probabilística de parâmetros de onda para análise de estruturas marítimas - Silva, Plinio Bueno Andrade (2018)
The aim of this dissertation is to analyze the joint distribution models based on the Nataf’s Transformation and on the Conditional Model in order to represent wave parameters such as significant wave height and peak period. The study uses numerical results from the WAVEWATCH III wave model for the Bacia de Santos area (Brazilian coast) and for the Norway Sea (Norway coast) as input data to create joint distribution models. It analyses the probabilities distribution which best fit into marginal distribution wave parameters as well as the performance of joint distribution models to represent them. For each of the sites, two sets of data have been analyzed: one set studies 11 years of numerical results (2006 to 2016) and the other studies just 2 years (2015 to 2016). Findings show that both models are able to represent wave data for the considered sites, but that Nataf’s Transformation is easier to use. In certain situations, however, and with the correct adaptations, the Conditional model can better represent certain aspects of wave characteristics.